Generation of CD34+ cells from human embryonic stem cells using a clinically applicable methodology and engraftment in the fetal sheep model - Kim, Jaehyup (2013)
Until now, ex vivo generation of CD34+ hematopoietic stem cells (HSCs) from human embryonic stem cells (hESCs) mostly involved use of feeder cells of non-human origin. While they provided invaluable models to study hematopoiesis, in vivo engraftment of hESC-derived HSCs remains a challenging task. In this study, we used a novel coculture system comprised of human bone marrow derived mesenchymal stromal/stem cells (MSCs) and peripheral blood CD14+ monocyte-derived macrophages to generate CD34+ cells from hESCs in vitro. Human ESC-derived CD34+ cells generated using this method expressed surface makers associated with adult human HSCs and up-regulated hematopoietic stem cell genes compared to human bone marrow-derived CD34+ cells. Finally, transplantation of purified hESC-derived CD34+ cells into the pre-immune fetal sheep, primed with transplantation of MSCs derived from the same hESC line, demonstrated multi-lineage hematopoietic activity with graft presence up to 16 weeks post-transplantation. This in vivo demonstration of engraftment and robust multi-lineage hematopoietic activity by hESC-derived CD34+ cells lends credence to the translational value and potential clinical utility of this novel differentiation and transplantation protocol.